In This Issue - David Briggs (ACHSM, 2020)
In this issue we start with an editorial that addresses the Corona virus COVID-19, a difficult task given the fast-moving nature of this pandemic. The editorial attempts to draw some lessons for us to consider from our experience of this event..... and the 6 articles included.....